Plano pedagógico para coordenadores de cursos: práxis educativa na Educação Profissional e Tecnológica - Souza, Pedro Santarém de (Brasil, 2022)
The proposal of this educational product is a Pedagogical Plan considering the main activities to guide educational praxis in the face of the challenges of course coordination, being the result of the research work related to Course Coordination in Professional and Technological Education of Secondary Level (EPTNM). In addition, this educational material includes a scope of educational actions related to the technical-pedagogical advice of the multiprofessional team of coordinators who operate courses in different technological axes in the offer of courses in the municipalities of the interior of Amazonas, therefore, our purpose is to favor the pedagogical work of the course coordinator, especially in the actions of planning, execution, analysis of educational results and improvement of the teaching and learningprocess. The educational product aims to contribute to the know-how ofthe course coordinator, having as a guideline the reflection on their educational praxis and the constant need to study and deepen the theoretical, scientific and methodological bases of Vocational and Technological Education (EPT), of this In this way, the material presents a plan for the organization of technical-pedagogical activities, based on the work developed by the multiprofessional team within the scope of the Technical Training Coordination sector (Fortec) of the Technological Education Center of Amazonas (Cetam). Therefore, the Pedagogical